Climate and society in Ireland from prehistory to the present - Kelly, James 1959-; Ó Carragáin, Tomás 1975- (Royal Irish Academy, 2021)
Can a long-term perspective on human adaptations to climate change inform Ireland's response to the crisis we face today? Climate and Society in Ireland is a collection of essays, commissioned by the Royal Irish Academy, that provides a multi-period, interdisciplinary perspective on one of the most important challenges currently facing humanity. Combining syntheses of existing knowledge with new insights and approaches, contributors explore the varied environmental, climatic and social changes that occurred in Ireland from early prehistory to the early 21st century. The essays in the volume engage with a diversity of pertinent themes, including the impact of climate change on the earliest human settlement of Ireland; weather-related food scarcities during medieval times that led to violence and plague outbreaks; changing representations of weather in poetry written in Ireland between 1600 and 1820; and how Ireland is now on the threshold of taking the radical steps necessary to shed its 'climate laggard' status and embark on the road to a post-carbon society.
"Journal monograph"
Einzelaufnahme eines Zeitschriftenbands
Keywords: Climatic changes / Ireland; Human beings / Effect of climate on / Ireland; Ireland / Environmental conditions; Ireland / Social conditions; Ireland / History; Aufsatzsammlung